Socio-economic profile of total edentulous patients rehabilitated at the Faculty of dentistry from the Federal University of Bahia - Samilly Evangelista Souza; Luciana Valadares Oliveira; Anderson Pinheiro de Freitas; Aline Araújo Sampaio; Guilherme Andrade Meyer; Marilisa Carneiro Gabarto (Editorial Ciencias Médicas, 2015)
Objective: Proposed to analyze the profile of elderly patients, edentulous, rehabilitated with complete dentures (PT) at the Faculty of Dentistry, Federal University of Bahia (FOUFBA). Method: This was a cross sectional study with 50 individuals of both genders. It was applied a structured questionnaire with questions about sociodemographic, housing, behavioral, general health conditions and care with PT. Results: it was found that the average age was 67.3 years and there was a predominance of females (86%). Regarding the educational level, 20% of respondents are illiterate, while 64% receive a minimum monthly salary and 96% live in their own house. The general health was good in 68%, and 24% didn't use medication. The time of edentulism in 76% of cases was more than 10 years, as well as brushing the denture was the most used method of cleaning. Conclusions: It was concluded that individuals had low levels of education and income, known factors associated with edentulism and evidenced in studies with similar populations, which may lead an increase in the number of denture wearers. Greater knowledge of this population favors the incentive to expand health strategies aimed at this age group in order to be prevented tooth loss.